2004
DOI: 10.1556/aalim.33.2004.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Processing Conditions on the Nontriacylglycerol Constituents of Sunflower Oil

Abstract: In this study samples of non-refined sunflower oils, obtained in industrial and laboratory scale by cold and hot pressing and hexane extraction, as well as sunflower oils from single refining steps were investigated. The content and composition of carotenoids, sterols, and the content of chlorophylls as well as oxidative stability were investigated. To obtain the data about the acidity and oxidative status of the oil samples, basic quality analyses of free fatty acid content (FFA), peroxide value (PV) and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Otherwise, sunflower oil it is not particularly rich in carotenoids with only 1-1.5 ppm of carotenoids (Gunstone, 2011). The major carotenoids in sunflower oil are xantophylls which reach up to 81% of the total (Rade et al, 2004).…”
Section: Others Terpenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, sunflower oil it is not particularly rich in carotenoids with only 1-1.5 ppm of carotenoids (Gunstone, 2011). The major carotenoids in sunflower oil are xantophylls which reach up to 81% of the total (Rade et al, 2004).…”
Section: Others Terpenoidsmentioning
confidence: 99%
“…• C, 0.59% w/w bleaching clay (TAIKO, type: Classic 1G, Malaysia) with mechanical stirring was used at vacuum 13 × 10 3 Pa for 30 min (Kreps et al, 2014) and carotenoids around 77% of the initial value (Rade et al, 2004). The decreases in total tocopherol contents due to bleaching step have been largely studied (Alpaslan et al, 2001;Ergönül and Köseoǧlu 2014;Kreps et al, 2014;Tasan and Demirci, 2005).…”
Section: Bleachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported lower FFA contents after neutralization by NaOH. Rade et al (2004) found that FFA value of crude and alkali refined sunflower oil were 1.60 and 0.06, respectively. Kuleasan and Tekin (2008) found that the FFA content of the crude soybean oil decreased from 0.56% to 0.14%–0.2% in 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, presence of tocopherols which are oil soluble natural antioxidant is important for oxidative stability while FFAs are prooxidative. Alteration of FFA concentration and addition of natural antioxidants to the oil are proven strategies for improvement of the oxidative stability of oils (Alpaslan et al, 2001; Brevedan et al, 2000; Fadda et al, 2022; Farhoosh & Pazhouhanmehr, 2009; Rade et al, 2004; Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%